Bifidobacteria exert species-specific effects on constipation in BALB/c mice. Issue 10 (8th September 2017) - Wang, Linlin; Hu, Lujun; Xu, Qi; Jiang, Tian; Fang, Shuguang; Wang, Gang; Zhao, Jianxin; Zhang, Hao; Chen, Wei
Abstract : Edible bifidobacteria exerted species-specific effects in relieving constipation. Abstract : Constipation is one of the most common gastrointestinal complaints worldwide. The aim of this study was to determine whether edible bifidobacteria ( Bifidobacterium longum, B. infantis, B. animalis, B. bifidum, B. adolescentis or B. breve ) exhibit interspecies differences in alleviating constipation induced by loperamide in BALB/c mice and to analyse the main reasons for the interspecies differences. BALB/c mice were given bifidobacteria by gavage once per day for 8 days. The primary outcome measures, which included related constipation indicators, and the secondary outcome measures, which included changes in the concentration of short-chain fatty acids in faeces and changes in the faecal flora, were used to evaluate the therapeutic effects of the edible bifidobacteria on constipation. The findings show that the six species of Bifidobacterium differed in their ability to relieve constipation. B. longum, B. infantis and B. bifidum were the most effective in relieving constipation, B. adolescentis and B. breve were partially effective and B. animalis was not effective. Furthermore, edible Bifidobacterium treated constipation by increasing the abundance of Lactobacillus and decreasing the abundance of Alistipes, Odoribacter and Clostridium . Higher concentrations of short-chain fatty acids were found in the faecal samples from the edible Bifidobacterium treatment groups. Meanwhile, an increased concentration of acetic acid could alleviate constipation. In conclusion, edible bifidobacteria exhibit interspecies differences in the alleviation of constipation. Meanwhile, bifidobacteria improved constipation symptoms by increasing the concentration of acetic acid and the relative abundance of Lactobacillus and reducing the content of Alistipes, Odoribacter and Clostridium .